PENGARUH YOUTUBE VIDEO TERHADAP PEMAHAMAN DAN KEMANDIRIAN PESERTA DIDIK PADA MUATAN PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Abdussalam; Pratiwi, Siska; Firmansyah, Ihwan; Andriani, Miranti Widi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Youtube is the most popular social media for several groups of people, from children to adults, which is an opportunity in the world of education. This research aims to look at the effect of YouTube videos on students' understanding and independence in elementary school mathematics learning content. This study used a pre-experimental design of the one-group pretset-posttest type, using one class using the pretest-posttest to be able to determine initial abilities related to the material being discussed. Based on the conclusions and results of the analysis using SPSS by the researchers with the conclusion that there is an effect of YouTube videos on the understanding and independence of students at UPTD SDN Kraton 5 Bangkalan. This is proven by the results shown in the Manova test where the significance value is 0.000 <0.05 so the conclusion is that there is an influence.